2018
DOI: 10.3892/ol.2018.8588
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the SphK1/ERK/p‑ERK pathway promotes autophagy in colon cancer cells

Abstract: Sphingosine kinase 1 (SphK1) is a master kinase that catalyzes the synthesis of sphingosine 1 phosphate and participates in the regulation of cell proliferation and autophagy. The present study aimed to assess the effects of the activation of the SphK1/extracellular signal-regulated kinase (ERK)/phosphorylated (p-)ERK pathway in the regulation of autophagy in colon cancer (HT-29) cells. Inverted fluorescence microscopy was used to detect the expression of green fluorescent protein (GFP) in the SphK1-overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 33 publications
0
26
1
Order By: Relevance
“…As it has been reported that iron chelation and ERK1/2 activation can both regulate the autophagy machinery [15,16,29,30], we wonder if autophagy is involved in this pathway. HA cells were treated with either C7, deferoxamine, Dp44mT, or their iron-precomplexed counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…As it has been reported that iron chelation and ERK1/2 activation can both regulate the autophagy machinery [15,16,29,30], we wonder if autophagy is involved in this pathway. HA cells were treated with either C7, deferoxamine, Dp44mT, or their iron-precomplexed counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…He et al ( 1 ) summarized the molecular mechanisms of chemoresistance in OS; however, the detailed molecular mechanisms by which SphK1 mediates doxorubicin resistance are unknown. Previous studies ( 27 , 29 , 30 ) reported that activation of the SphK1/ERK/p-ERK signaling pathway in colon cancer cells promoted autophagy, which is one of a number of mechanisms that have been reported to be responsible for chemoresistance.…”
Section: Discussionmentioning
confidence: 96%
“…In 2006, Bonhoure et al ( 25 ) reported that SphK1 contributes to MDR-associated chemoresistance in acute myeloid leukemia. The role of SphK1 in chemoresistance has also been investigated in several different types of cancer, including breast ( 26 ), colon ( 27 ) and gastroesophageal cancer ( 28 ), as well as hepatocellular carcinoma ( 12 ). A study conducted by Wang and Wu ( 12 ) reported that SphK1 expression was associated with poor prognosis and oxaliplatin resistance in hepatocellular carcinoma ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang and co-workers demonstrated that microRNA-506-3p was able to inhibit autophagy through targeting Sphk1 in osteosarcoma cells [22]. In another study, authors demonstrated that Sphk1/ERK/p-ERK pathway involved in the induction of autophagy in colon cancer cells [23]. Inconsistently, it was reported that the inhibition of Sphk1 expression could induce autophagy in head and neck squamous cell carcinoma cells [24].…”
Section: Sphk1 Gene Plays An Important Role In a Variety Of Diseases mentioning
confidence: 98%